Órtese de tornozelo: efeito sobre a razão de pico torque muscular eversor excêntrico/inversor concêntrico do tornozelo durante simulação do basquetebol - Castro, Alex [UNESP] (2011)
The ankle sprains represent the most common injuries in sports and basketball. In this sense, the use of ankle bracing and strength capacity analysis of the ankle evertor and invertor muscles, have been suggested as preventive measures and important tools for identifying risk factors associated with ankle sprains. However, questions still persist as to effect of the use ankle bracing on biomechanical variables related to the stability of the ankle. For this reason, this study aims to analyze the effect of the use of ankle bracing on peak torque (PT) of ankle evertor and invertor muscles and on eccentric evertor/concentric invertor torque ratio (EVEECC/INVCON), during the basketball match-play simulation. Ten healthy college basketball players, without mechanics or functional ankle instability performed a laboratory-based protocol representative of work rates observed during basketball match-play, in two different situations, with and without use of ankle bracing. The test was composed of a succession of intermittent physical effort equally distributed in four periods of 10 minutes each, considering the mechanical and physiological demands of a basketball match-play. Prior to the start of the trial (Evaluation 1) and after 2° (Evaluation 2) and 4° (Evaluation 3) periods, the subjects performed five maximal isokinetic concentric and eccentric contractions of ankle invertor and evertor muscles, separated by two minutes rest, at 60 °/s and 120 °/s. After testing for normality of data distribution with the Shapiro-Wilk test, was used the ANOVA repeated measures for two factors and post-hoc Bonferroni test for comparison of variables between assessments. Was adopted p < 0.05. There was no significant difference for PT and EVEECC/INVCON torque ratio between assessments. There was a decrease in PT EVEECC at 60º/s and 120º/s for the ...(Complete abstract click electronic access below)